A tool for model conversion between simulators of grid computing - Furlanetto, Gabriel C. [UNESP] (2015)
High performance computing systems usually have a high usage cost, even with the use of shared systems, such as grids and clouds. To reduce such costs it is necessary to optimize system's utilization through performance analysis of one's application. This can be done through simulators designed specifically for performance prediction/analysis, such as GridSim and Simgrid, among several grid computing simulators developed in the past years. Unfortunately, there is no compatibility between these simulators, making models developed for one of them unusable for the others. This is even more problematic when one notices that the models for these simulators demand coding of several complex functions, making model reuse hard to achieve. In this paper we present an extension made to iSPD (iconic Simulator of Parallel and Distributed Systems), which is already an easy-to-use grid simulator, in order to enable model conversions. With this extension an user is able to read models written for GridSim or Simgrid, converting them into the iconic models used by iSPD. He/she is also able to convert iSPD models into models for those simulators. The process of conversion is discussed, showing the actions necessary to convert the models. A comparison between the simulation of models built using each simulator is presented.